The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/cbdv.202300743
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Hybrid Nanoflowers Using Glycine and Phenylalanine and Investigation of Their Catalytic Activity

Abstract: In the context of the proposed work, two different amino acids (Glycine, Phenylalanine) have interacted with copper ions in a phosphate buffer (PBS) in place of enzymes. This interaction resulted in the nucleation of copper phosphate crystals and the formation of flower‐shaped amino acid‐copper hybrid nanostructures (AA‐hNFs), which grew through self‐assembly. While Cu (II) ions in the structure of AA‐hNFs were used as Fenton's agent for the catalytic activity. SEM, energy dispersive X‐ray spectroscopy, X‐ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Enzymes play a crucial role in the metabolism of organisms and technological applications . Recent studies have shown that amino acids can coordinately self-assemble with metal ions that exhibited excellent catalytic activity similar to natural enzymes. Makam et al synthesized a layered supramolecular amyloid-like ordered structure (Phe-Zn(II)) by assembling Phe with Zn 2+ in alkaline solution (Figure a), showing an excellent esterase catalytic efficiency of 76.54 M –1 s –1 , which exceeded the reported artificial biomolecular-based carbonic anhydrase mimetics. In addition, Phe-Zn(II) exhibited reversible catalysis of the hydration reaction of CO 2 in the presence of water, converting CO 2 into bicarbonate and protons, thus reducing the pH value .…”
Section: Applications Of Amino Acid Based Materialsmentioning
confidence: 99%
“…Enzymes play a crucial role in the metabolism of organisms and technological applications . Recent studies have shown that amino acids can coordinately self-assemble with metal ions that exhibited excellent catalytic activity similar to natural enzymes. Makam et al synthesized a layered supramolecular amyloid-like ordered structure (Phe-Zn(II)) by assembling Phe with Zn 2+ in alkaline solution (Figure a), showing an excellent esterase catalytic efficiency of 76.54 M –1 s –1 , which exceeded the reported artificial biomolecular-based carbonic anhydrase mimetics. In addition, Phe-Zn(II) exhibited reversible catalysis of the hydration reaction of CO 2 in the presence of water, converting CO 2 into bicarbonate and protons, thus reducing the pH value .…”
Section: Applications Of Amino Acid Based Materialsmentioning
confidence: 99%
“…Recent years, many efforts have focused on this topic to develop biomolecule-inorganic hybrid nanoflowers with potential applications ( Cui and Jia, 2017 ). Demirbaş et al (2023) developed a facile synthesis method for hybrid nanoflowers using glycine and phenylalanine (AA-hNFs). The AA-hNFs exhibited a uniform flower shape and peroxidase-like activities.…”
mentioning
confidence: 99%